Design of Interference Measurement System with Crystal - Shuyan Ren; Yonggang Yang; Hailong Duan (Institute of Advanced Engineering and Science, 2013)
A kind of interference measurement system with crystal is designed, which is not influenced much by other factors such as vibration for the property of common path. For the distance measurement, the phase of fringes is calculated on the oblique incident holography to avoid effects of fringe curvature, backup and light fluctuation. But the measurement result is affected by the uniformity of the crystal, and another method of adjusting position based on normal incident holography is also discussed. B-splines function is used to calculate zero position in normal incident holography, which is fitted over the patch image around gray extreme points of the stripes obtained by gray projection. Experiment results show that combining the normal and oblique incident holography reduce the repeatability error of the system and improve the measurement precision effectively. DOI: http://dx.doi.org/10.11591/telkomnika.v11i3.2303